Clinical Presentation and Predictors of Acute Coronary Syndrome: A Cross Sectional Study - Bista, Madhab; Nepal, Rajesh; Katuwal, Sushant; Mehta, Ram Kumar (Annapurna Journal of Health Sciences, 2023)
Introduction: Acute coronary syndrome (ACS) is an umbrella term for conditions when ischemia to the heart muscles is prolonged and not immediately reversible. Depending on its clinical presentation, prompt management is required. The objective of this study was to explore the clinical profiles and predictors of mortality among patients diagnosed with ACS. Methods: A hospital based prospective cross sectional study was conducted among 200 patients at Nobel Medical College Teaching Hospital from 15 April 2020 to 15 March 2021. Total enumeration technique was used. Data was collected using specifically designed proforma, and analyzed on SPSS version 23. Mean, standard deviation, Chi square and Odds Ratio (OR) was calculated. P value <0.05 was considered statistically significant. Results: Majority of the respondents were in the age group 56-65 years with mean ±SD (62.9± 10.6) years. Chest pain (p= 0.003), Nausea (p=0.024), Dyslipidemia (p=0.000), HDL (p=0.000), and Hypertension (p=0.03) had statistically significant differences between male and female. Breathlessness (p=0.013, OR 3.7), syncope (p=0.021, OR 3.6), time of onset (p=0.004), increased LDL (p=0.023, OR 3.1), ventricular tachycardia (p=0.003, OR 7.6) and conservative management approach (p=0.000, OR 7.5) has statistically significant differences in terms of patient's outcome. Conclusion: Male patients had significantly increased clinical presentation. The strongest predictors of mortality were male sex, breathlessness, syncope, increased time of onset of pain, increased LDL, ventricular tachycardia and conservative management.